ACCOMPLISHMENTS AND FUTURE OF BIOLOGICAL CONTROL AND INTEGRATED CONTROL IN BRAZIL – PART 3 - Sverre Hagen, Kenneth (REVISTA DE AGRICULTURA, 2025)
The entomologist Kenneth Sverre Hagen, professor of the University of California at Berkeley, and that moment working in the Michigan State University, was in Brazil for a three month period in 1977 as a consultant in the Program of Superior Agricultural Education (Programa de Educação Agrícola Superior – PEAS) of the Ministry of Brazilian of Education and Culture. During this period (from July to September), Professor Hagen trained and changed experiences with docents (university professors) and researchers in several fields mainly in the Biological Control of Insects and Pests using ESALQ (Superior College of Agriculture) as a basing point. He visited other Brazilian Universities and Research Institutions. All of the activities are presented in the Report Biological and Integrated Control of Insects in Brazil (Controle Biológico e Controle Integrado de Insetos no Brasil: Realizações e Futuro), a never published document. During his stay in Brazil, he was accompanied by a professor from the Entomology departament, responsible for rescuing this report. Of an invaluable historical nature, the report will be published in three parts in the Brazilian Journal of Agriculture (BJA), opening the “Unpublished historical papers” section.